Structural Model Analysis of The Relationship Between Cross-National Trade, Use of Technology and Labor Costs - Moh. Samsul Arifin; Teguh Prakoso; Aprilya Dwi Yandari; Rina Apriliani; Abdurohim (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to quantify the costs of job mobility, emphasizing the differences in costs faced by workers with different qualifications. Our analysis uses the Ordinary Least Squares and Instrumental Variables. The impact of trade and technological reforms on workers' welfare is largely dependent on the level of economic flexibility. In this context, high labor mobility costs become an important factor in analyzing the impact of trade policies. Despite workers' high mobility between job sectors, traditional theory suggests that this flexibility may not be as strong due to the greater influence of non-financial factors. This suggests that there needs to be a different policy approach to managing the impact of trade and technology reforms to ensure worker well-being and overall economic stability. Trade and technology reforms often result in increased efficiency, but they also incur certain costs. The finding that unskilled workers have higher mobility costs than semi-skilled workers is interesting, as it suggests that there are greater barriers for unskilled workers to move between employment sectors. The impact of slow adjustments in the labor market due to high mobility costs is also important, as this indicates that the economy takes a long time to adapt to changes, both from trade and technological reforms. This has long-term implications for the well-being of negatively affected workers, depending on the particular model parameters. It is important to continue to deepen our understanding of the costs of mobility and labor market adjustment, as this will help in designing better policies to support workers impacted by economic reform and change.